Pengaruh Sosialisasi Pengetahuan Perpajakan dan Sanksi Pajak Terhadap Wajib Pajak Orang Pribadi Sebagai Variabel Intervening - M Rangga Arofhy; Ruswan Nurmadi; Liza Novietta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of tax socialization, tax knowledge, and tax sanctions on private person taxpayer compliance with taxpayer awareness as an intervening variable in KPP Pratama Medan Polonia. The sample in this study was 100 pivate person taxpayers registered at KPP Pratama Medan Polonia. The data analysis technique used was path analysis. The results showed that tax socialization and tax knowledge had a significant effect on taxpayer awareness, while tax sanctions had no significant effect on taxpayer awareness. tax sanctions and taxpayer awareness have a significant effect on taxpayer compliance, while taxation socialization and tax knowledge have no significant effect on taxpayer compliance. Tax sanctions and taxpayer awareness affect taxpayer compliance.Taxpayer awareness cannot intervene tax socialization, tax knowledge and tax sanctions on private person taxpayer compliance.